Management of a unilateral non‐healing corneal ulcer and uveitis in a laughing kookaburra (Dacelo novaeguineae). Issue 1 (17th October 2014) - Sabater, Mikel; Pérez, Marisa
Abstract : A six‐year‐old male laughing kookaburra ( Dacelo novaeguineae ) was presented for evaluation of unilateral ocular lesions. The bird had a non‐healing corneal ulcer and uveitis in the left eye. The combination of medical (oral meloxicam and ciprofloxacin eye drops) and surgical debridement with dry cotton‐tip applicators after prepping the cornea with povidone‐iodine solution proved to be effective in order to achieve a complete healing of the cornea and to control the uveitis observed in the present case. This case report is written in order to provide more information about the management of non‐healing corneal ulcers in avian species.